Alterations in redox homeostasis during recovery from unexplained underperformance syndrome in an elite international rower - Lewis, N. A.; Redgrave, A.; Homer, M.; Burden, R.; Martinson, W.; Moore, B.; Pedlar, C. R. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To examine a diagnosis of unexplained underperformance syndrome (UUPS, or overtraining syndrome) in an international rower describing a full recovery and return to elite competition the same year. Methods: On diagnosis and 4 and 14 mo postdiagnosis, detailed assessments including physiological, nutritional, and biomarkers were made. Results: Clinical examination and laboratory results for hematology, biochemistry, thyroid function, immunology, vitamins, and minerals were unremarkable and did not explain the presentation and diagnosis. Redox biomarkers including hydroperoxides, plasma antioxidant capacity, red blood cell glutathione, superoxide dismutase, coenzyme Q10, vitamin E (a- and ?-tocopherol), and carotenoids (lutein, a-carotene, ß-carotene) provided evidence of altered redox homeostasis. The recovery strategy began with 12 d of training abstinence and nutritional interventions, followed by 6 wk of modified training. At 4 mo postintervention, performance had recovered strongly, resulting in the athlete`s becoming European champion that same year. Further improvements in physiological and performance indices were observed at 14 mo postintervention. Physiologically relevant increases in concentrations of carotenoids were achieved at each postintervention time point, exceeding the reported critical-difference values. Conclusions: Increasing athlete phytonutrient intake may enhance recovery and tolerance of training and environmental stressors, reducing the risk of unexplained UUPS. Alterations in redox homeostasis should be considered as part of the medical management in UUPS. This is the first reported case study of an elite athlete with alterations in redox homeostasis in conjunction with a diagnosis of UUPS.